Une caractérisation des services environnementaux à dimension paysagère produits dans les espaces ruraux - Olivier Aznar (Développement Durable et Territoires)
This paper presents the first results of a research on the economic analysis of environmental services with landscape dimension, more particularly those produced in rural areas. Thanks to the economics of services, the author proposes a definition of the environmental service. Then, he outlines a typology based on the production of the environmental service. The last part presents an empirical illustration in some communes of the Puy de Dôme (France), located in the French Regional Nature Park of the Volcanoes of Auvergne.